Uji Penyembuhan Luka dan Potensi Iritasi Ekstrak Etanol Daun Binahong (Anredera cordifolia (Ten) Steenis) - SRI HARTATI YULIANI (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
Binahong (Anredera cordi olia (Ten) Steenis) has been used as wound healing in traditional Indonesian medicine. The aim of this study was to examine the wound healing activity and irritation potency of ethanolic extract of Anredera cordifolia (Ten) Steenis. Dry Binahong leaves were ground and screened with mesh no 40. Dry Binahong leaves were macerated with 10 times of volume of 96% ethanol for 90 minutes with constant agitation (200 rpm). It was screened and concentrated until the liquid would be a quarter. Then the extract was incorporated to gel base as 2,5%; 5%; 10% and 20%. Incision wound method was employed to activity test of wound healing. Male mice (strain Swiss), weight between 25 ~ 30 g, was used to this test. The male mice were classified into 7 groups i.e. negative control, control vehicle, positive control and 4 groups of sample. The extract then was assessed to irritation potency using HET-CAM method. Lactic acid was used as the positive control for irritation assessment. The result of this study stated that the highest activity of wound healing was shown by the sample containing 5% of ethanolic extract. The percentage activity of wound healing was 63,3%. Irritation appeared on the 10% and 20% ethanolic extract of binahong leaves.